2018
DOI: 10.3233/jad-170838
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lithium Treatment Increases Telomere Length in Parietal Cortex and Hippocampus of Triple-Transgenic Alzheimer’s Disease Mice

Abstract: Telomere length (TL) is a biomarker of cell aging, and its shortening has been linked to several age-related diseases. In Alzheimer's disease (AD), telomere shortening has been associated with neuroinflammation and oxidative stress. The majority of studies on TL in AD were based on leucocyte DNA, with little information about its status in the central nervous system. In addition to other neuroprotective effects, lithium has been implicated in the maintenance of TL. The present study aims to determine the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…This limitation is particularly relevant, as several studies showed a significant effect of psychotropic medications on TL or the expression and activity of telomerase (the enzyme responsible for controverting the shortening of telomeres in certain cell types) in animal or human studies. Findings are particularly congruent for lithium (Cardillo et al, ; Coutts et al, ; Martinsson et al, ; Powell, Dima, Frangou, & Breen, ; Squassina et al, ; Wei, Backlund, Wegener, Mathe, & Lavebratt, ), but some evidence has also been reported for antidepressants (Hough et al, ; Rasgon, Lin, Lin, Epel, & Blackburn, ; Wolkowitz et al, ). In the current study, we tested the correlation between lifetime duration of treatment with antidepressants and LTL but found no significant effect.…”
Section: Discussionmentioning
confidence: 95%
“…This limitation is particularly relevant, as several studies showed a significant effect of psychotropic medications on TL or the expression and activity of telomerase (the enzyme responsible for controverting the shortening of telomeres in certain cell types) in animal or human studies. Findings are particularly congruent for lithium (Cardillo et al, ; Coutts et al, ; Martinsson et al, ; Powell, Dima, Frangou, & Breen, ; Squassina et al, ; Wei, Backlund, Wegener, Mathe, & Lavebratt, ), but some evidence has also been reported for antidepressants (Hough et al, ; Rasgon, Lin, Lin, Epel, & Blackburn, ; Wolkowitz et al, ). In the current study, we tested the correlation between lifetime duration of treatment with antidepressants and LTL but found no significant effect.…”
Section: Discussionmentioning
confidence: 95%
“…All animal had access to food and water ad libitum. Lithium-treated mice also received a bottle with 0.9% NaCl for ad libitum intake, according to previous experience in our lab (Cardillo et al, 2018). Treatments lasted for 34 weeks, until animals reached 11 months of age, when it is accepted that mice become middle aged.…”
Section: Treatment Groupsmentioning
confidence: 99%
“…In this study, normalization of the telomerase gene expression and protein activity was not accompanied by increase of TL, suggesting that changes in TL might occur in a much slower way, compared to changes in the enzyme activity [71]. Intriguingly, Cardillo and coworkers [72] showed that chronic lithium treatment (eight months) increased TL in the hippocampus and parietal cortex in a transgenic mouse model of Alzheimer’s disease [72]. Consistent with these observations, clinical studies suggest that the duration of lithium treatment is positively associated with TL in BD patients with a history of long-term treatment with this drug [48,50].…”
Section: Telomeres and Psychotropic Medicationsmentioning
confidence: 76%